HUBUNGAN DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP PADA PASIEN HEMODIALISA PENYINTAS COVID - 19 DI RSUD KOJA - Nenden Purwaningsih, (2021)
Kidney failure is a disease characterized by decreased function of the kidneys. Kidneys are not able to filter optimally, causing a buildup of toxins in the body. Kidney disease is the largest contributor to death in the world. One treatment for kidney failure is hemodialysis, an action that functions to remove toxins from the body by washing dirty blood back into clean. In early 2020, a virus emerged, namely the covid-19 virus. A virus that mutates very quickly causes respiratory problems to cause death. Those exposed to COVID-19 must undergo isolation. This study aims to find out how relationship between family support and the quality of life of hemodialysis patients for COVID-19 survivors is. The research design is analytical description with a cross sectional approach. Total respondents were 41 people. The results of the analysis stated that there was no relationship between the descriptions of respondents' characteristics including age, gender, education, occupation, duration of exposure to COVID-19 with p value > 0.05. However, the results of the analysis stated that there was a relationship between family support and the quality of life of hemodialysis patients who survived COVID-19 with a p value < 0.05 (p value = 0.001).